Incorporating Target Shedding Into a Minimal PBPK–TMDD Model for Monoclonal Antibodies. (29th January 2014) - Li, L; Gardner, I; Rose, R; Jamei, M
Abstract : Shedding of a pharmacological target from cells, giving rise to a soluble target that can also bind therapeutic proteins, is a common phenomenon. In this study, a minimal physiologically based pharmacokinetic model was used to simulate the pharmacokinetics of trastuzumab and the simultaneous binding of the compound to soluble (in blood and tissue interstitial space) and membrane‐bound (in the tissue interstitial space) forms of human epidermal growth factor receptor 2 (HER2). The parameter values describing binding of trastuzumab to HER2 were largely derived from in vitro data, and the effects of varying HER2 levels, the affinity difference between membrane‐bound HER2 and shed antigen, and slow binding kinetics were investigated. The model simulates a sharp decrease in trough drug concentrations at concentrations of soluble target between 500 and 1, 000 ng/ml in plasma. This corresponds with the clinical concentration range of soluble target wherein changes in half‐life of trastuzumab have been observed. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e96; doi:10.1038/psp.2013.73 ; published online 29 January 2014